Pengaruh Intensitas Bermain Game Mobile Legends: Bang Bang Terhadap Kedisiplinan Beribadah Shalat Lima Waktu Mahasiswa PAI UMS dalam Perspektif Pendidikan Agama Islam - Dzaki Fakhri Qois; Hafidz Hafidz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of the intensity of playing Mobile Legends: Bang Bang on the discipline of praying the five daily prayers of students of the Islamic Religious Education Study Program (PAI) of the University of Muhammadiyah Surakarta (UMS) from the perspective of Islamic Religious Education. This study uses a descriptive qualitative approach with a phenomenological perspective. The research informants are UMS PAI students who actively play Mobile Legends: Bang Bang. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data validity was tested using source triangulation, technical triangulation, and member check. Data analysis was carried out through the stages of data collection, data condensation, data presentation, and conclusion drawing. The results showed that the intensity of playing Mobile Legends in some students was quite high, characterized by the frequency of playing almost every day, playing duration between 1-6 hours per day, high focus of attention on the game, and strong emotional involvement. The high intensity of playing affects the discipline of praying the five daily prayers, especially in the form of delays in performing prayers, especially the Subuh and Isha prayers, there were even informants who had missed prayers because they were too focused on playing. Based on the behaviorism theory of B.F. According to B.F. Skinner, this behavior is formed through a process of stimulus, response, and reinforcement obtained during game play. From an Islamic Religious Education perspective, playing games is essentially permissible as long as it does not neglect religious obligations. Therefore, Islamic Religious Education students are expected to be able to control the intensity of their play and prioritize prayer.